Design of LED Information Display for High Speed EMUs - 刘东亮; 张凌云; 陈天喜 (机车电传动)
This paper introduced the project development of localization LED information display, which was part for 200 km/h, 300 km/h EMUs. Emphasis had been put on the scheme design for TPX31 passenger information display. The problems happed during production process and its solutions had also been analyzed. This paper puts forward some innovative design concept, summaries some experiences and prospect the application of LED information display in other fields.